Digital institutional repositories: Comparative analysis between SEDICI (Argentina) and Kérwá (Costa Rica) - Sandí Delgado, Juan Carlos (2016)
The objective of this work is to compare two digital international institutional repositories to find convergences and divergences in regards to the administration and operation of data, information and content. Also, it contributes to broaden the panorama and knowledge related to the importance and impact of digital repositories in Higher Education Institutions (Instituciones de Educación Superior - IES). The repositories studied belong to the Dissemination Service of Intellectual Creation (Difusión de la Creación Intelectual - SEDICI), main institutional repository of La Plata National University (UNLP), Argentina and Kérwá, main institutional repository of the University of Costa Rica (UCR), Costa Rica. A methodological quantitative focus was developed to accomplish the investigation objective.  The information was collected through questionnaires applied to the people responsible of the administration of both repositories and a bibliographical revision of electronic documents, such as articles published in congresses, international magazines, among others. The analysis was implemented following these criteria and characteristics: resources representation, interoperability, normalization, visibility, preservation, among others. It was concluded that digital institutional repositories have become an innovation trend for IES. They use and promote technological tools to produce significant changes in regards to information use and management.  Also, the digital repositories analyzed converge in aspects such as: software, metadata, normalized numbers, resources representation, accessibility, identifier, author rights, contents deposit, searchers and preservation. They diverge in regards to: interoperability, digitalization process, remote deposit, visibility, licensing and divulgation.